Work Life Balance Ditinjau dari Beban Kerja Polisi - Aura, Raissa Rahma; Lutfiyani, Mawarda; Manik, Samantha Petricia; Prameswari, Audria Sharon; Supriyadi, Tugimin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Police officers certainly have a sense of being fortunate in getting a balance between work and responsibilities at home. Work-life balance problems usually occur when someone finds it difficult to achieve balance between personal life and work life. Stress is a psychological condition caused by excessive workload. The aim of this research is to find work-life balance related to the workload of a police officer. This research methodology uses a literature review. Based on the findings of a literature search regarding the influence of workload on work-life balance for police, it can be said that high workload has a significant impact on work-life balance for police.